Hedging in Modern English - Harutyunyan, Nona (Armenian Folia Anglistika, 2013)
The article aims to investigate the functional value of hedges and to trace their development process in linguistic literature and scientific discourse. An attempt is made to provide a short definition of hedges, to identify its types and to indicate the main fields of their use. Hedges can express politeness, uncertainty, mitigation, indecisiveness thereby decreasing the responsibility of the speaker for his demands and suggestions.